Use of spectral kurtosis for improving signal to noise ratio of acoustic emission signal from defective bearings - Ruiz Cárcel, Cristóbal; Hernani-Ros, E.; Cao, Yi; Mba, David (Springer, 2014)
The use of Acoustic Emission (AE) to monitor the condition of roller bearings in rotating machinery is growing in popularity. This investigation is centred on the application of Spectral Kurtosis (SK) as a denoising tool able to enhance the bearing fault features from an AE signal. This methodology was applied to AE signals acquired from an experimental investigation where different size defects were seeded on a roller bearing. The results suggest that the signal to noise ratio can be significantly improved using SK.
Keywords: Acoustic emission; Signal-to-noise ratio; Spectral Kurtosis; Roller bearings